Improving Adolescent Life Skills through Sport Programs at the Child Correctional Institution - Akhmad Sobarna; Ahmad Hamidi (Universitas Pendidikan Indonesia, 2023)
This study was aimed to examine the integration of life skills in sport training programs. Participants of this study were adolescent aged 14 -19 years, involving 22 adolescents (11 adolescents receiving the Life Skill program, 11 adolescents receiving regular exercise training without life skill programs). Sampling technique used in this study was the intact group technique. The method used was experimental method with a quasi-experiment model and pre-test post-test control group design. The instrument of this study was an instrument from Cronin and Allen (2017) containing eight life skills taught in a sports training program. The results of this study indicate that the sport program containing life skills in a structured and deliberate manner had an influence on the life skills of adolescent at Correctional Institution in Bandung City. The highest increase of life skill component in the integrated life skill group was leadership with the average development of 1.25. Meanwhile, the life skill component that had the highest increase in the non-integrated life skill group was the emotional skill with the average development of 0.70. In conclusion, the provision of sport programs integrated with life skills in a structured and deliberate manner is proven to be able to develop life skills and could improve the life skill of adolescent higher than sports programs that are not structured and intentionally integrated with life skills.